Study of Mechanical Properties of (Al-Cu-Mg) Alloy Matrix Composite - Salih, Sahama E.; Al-Jnabi, Mervit M. (Al-Khwarizmi Engineering Journal, 2012)
The present research had dealt with preparing bars with the length of about (13 cm) and adiametar of (1.5 cm) of composite materials with metal matrix represented by (Al-Cu-Mg) alloy cast enforced by (ZrO2) particles with chosen weight percentages (1.5, 2.5 ,3.5, 5.5 %). The base cast and the composite materials were prepared by casting method by uses vortex Technique inorder to fix up (ZrO2) particles in homogeneous way on the base cast. In addition to that, two main groups of composite materials were prepared depending on the particles size of (ZrO2) , respectively. The study also contained the effect of insolution heat treatment at (505 0C) and the following forming process in addition to aging process at (185 0C) during different periods for all the prepared models. Also we caried on the study of the effect of reinforcement the base cast process with zerconia particles (ZrO2) on some of its mechanical properties. The optical microscopy test should that the microstructures of the composite materials having fine grains as comparet with large grains more of the base cast. As for hardness test & tensile test results showed an increase in hardness & tensile strength in addition to the increase in (ZrO2) that was added to reach the highest values when the weighted percentage of 3.5% and the amount of(140H.V),(570MPa) respectively. It was noted that the ductile values are reduced continuously with the increase of the added (ZrO2) . The effect of particle size of (ZrO2) particles on the mechanical properties, it was noted that there was a little reduction in the values of hardness and tensile strength with an increase of the particle size of (ZrO2) bat remains higher than in the base cast and the amount of(110H.V),(210MPa) respectively. While there was an increase in the ductilevalues with increasing the particle size but they still less than in the base cast.